Australia : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Australia. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that the Australia's economy is now facing a large transition as the mining investment boom winds down and the terms of trade has fallen back. Growth has been below trend for two years. Annualized GDP growth was about 2.2 percent in the first half of 2015, with particularly weak final domestic demand, and declining public and private investment. Capacity utilization and a soft labor market point to a sizeable output gap. Nominal wage growth is weak, contributing to low inflation. The FY2015/16 Budget projects a return to surplus in 2019-20.